Experience with prolonged induced hypothermia in severe head injury - Bernard, Stephen A (BioMed Central, 1999)
BACKGROUND: Recent prospective controlled trials of induced moderate hypothermia (32⌓34°C) for relatively short periods (24⌓48 h) in patients with severe head injury have suggested improvement in intracranial pressure control and outcome. It is possible that increased benefit might be achieved if hypothermia was maintained for more periods longer than 48 h, but there is little in the literature on the effects of prolonged moderate hypothermia in adults with severe head injury. We used moderate induced hypothermia (30⌓33°C) in 43 patients with severe head injury for prolonged periods (mean 8 days, range 2⌓19 days). RESULTS: Although nosocomial pneumonia (defined in this study as both new chest radiograph changes and culture of a respiratory pathogen from tracheal aspirate) was quite common (45%), death from sepsis was rare (5%). Other findings included hypokalaemia on induction of hypothermia and a decreasing total white cell and platelet count over 10 days. There were no major cardiac arrhythmias. There was a satisfactory neurological outcome in 20 out of 43 patients (47%). CONCLUSION: Moderate hypothermia may be induced for more prolonged periods, and is a relatively safe and feasible therapeutic option in the treatment of selected patients with severe traumatic brain injury. Thus, further prospective controlled trials using induced hypothermia for longer periods than 48 h are warranted.